Research trends of inflammation in autism spectrum disorders: a bibliometric analysis - Chen, Yajing; Du, Xiaohuan; Zhang, Xianming; Li, Fang; Yuan, Shuwei; Wang, Wenjing; Zhu, Zengyan; Wang, Mei; Gu, Chao (Frontiers in Immunology, 2025)
BackgroundInflammation has been recognized as a significant factor in the pathophysiology of autism spectrum disorders (ASD), which have garnered increasing scholarly attention over the past few decades. This study aims to explore research trends related to inflammation and ASD through bibliometric analysis.MethodA comprehensive literature search was conducted in the Web of Science Core Collection (WoSCC) on August 28, 2024. This study was restricted to literature published in English. The bibliometric analysis utilized VOSviewer, CiteSpace, and the R package “bibliometrix” to visualize collaborations, keyword co-occurrences, and emerging research trends.ResultsA total of 1,752 articles addressing inflammation and ASD were published, demonstrating a consistent upward trend in research output. The United States emerged as the country with the highest volume of publications. Saleh A. Bakheet was identified as the most prolific authors, significantly contributing to the literature with 54 publications. The University of California System was recognized as the most productive institution in this area of study. The journal of Brain Behavior and Immunity was noted as a prominent venue for publication in this field, exhibiting high citation metrics that reflect its considerable influence. The keyword “children” was the most frequently occurring term, with other significant terms including “oxidative stress” and “brain.” The keyword burst analysis revealed notable periods of increased research focus on topics such as “inflammatory bowel disease,” “cytokine production,” “neurodevelopmental disorders,” and “microbiota.”ConclusionThis bibliometric analysis highlights the growing scholarly attention devoted to the relationship between inflammation and ASD. Significant contributions and emerging trends emphasize the pivotal role of neuroinflammation in ASD, indicating a necessity for further exploration in this domain.